GLOSSARY OF TERMS ON COVID-19 - Campos-Rivero, Oscar (2023)
In this time of the pandemic, experts have tried to explain different aspects related to the coronavirus without much success because each one used different meanings or addressed the population with technical language, which was often incomprehensible to the population. In this sense, the objective of this work was to develop a glossary of the most commonly used terms about the coronavirus pandemic in Peru. In addition, a bibliographic review was made in the literature referring to health, economics, and the social sciences. It is concluded that professionals, especially health professionals, should unify criteria in terms of meanings and use less technical language to positively affect their messages to the population and thus comply with prevention measures. Keywords: coronavirus – COVID-19 – glossary – information – pandemic